1947
DOI: 10.1021/ie50456a018
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption - A Tool in the Preparation of High-Purity Saturated Hydrocarbons

Abstract: Mixtures of isomeric saturated hydrocarbons, including geometric isomers, can be separated by adsorption on silica gel or activated carbon; activated alumina gives very little separation. Data are given on the separation of many binary synthetic mixtures, including paraffin-paraffin, paraffin-naphthene, and naphthene-naphthene types.Most of these systems give S-type isotherms on silica gel and U-type isotherms on carbon. The effect of hydrocarbon type and molecular weight on adsorbability is discussed. The the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1948
1948
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Also, the fractionation of these components is unsymmetrical and, in both cases, the first portion of the filtrate contains the least strongly adsorbed component in a substantially pure condition; the last part of the hydrocarbon portion of the filtrate consists of a mixture which is substantially nonfractionating. The occurrence of nonfractionating mixtures is not uncommon with hydrocarbon systems as has also been observed by Hirschler and Amon (5). In terms of the theory previously given, the separation factor for a nonfractionating mixture is unity.…”
Section: Applicationssupporting
confidence: 64%
“…Also, the fractionation of these components is unsymmetrical and, in both cases, the first portion of the filtrate contains the least strongly adsorbed component in a substantially pure condition; the last part of the hydrocarbon portion of the filtrate consists of a mixture which is substantially nonfractionating. The occurrence of nonfractionating mixtures is not uncommon with hydrocarbon systems as has also been observed by Hirschler and Amon (5). In terms of the theory previously given, the separation factor for a nonfractionating mixture is unity.…”
Section: Applicationssupporting
confidence: 64%
“…There is not much literature on adsorbate-adsorbent interaction. The only literature available is covered in patents [13][14][15][16][17][18][19][20][21]. With the little that has been established it has been concluded that the selection of adsorbent is more of an art than science.…”
Section: Smb Parameters 71 Adsorbate-adsorbent Interactionmentioning
confidence: 99%
“…As a rule of thumb silica and alumina are used for polar components. Equilibrium data published in the literature [13][14][15][16][17][18][19][20] can be used to identify a suitable adsorbent. The order of affinity of various chemical species is; saturated hydrocarbons, aromatic hydrocarbon, halogenated hydrocarbons, ethers, esters, ketones, amines, alcohols, carboxylic acids [10].…”
Section: Adsorbents Used In the Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…was described by Lindeboom (105). In the field of hydrocarbons, Hirschler and Amon (76) found that the highest purity was obtained for 2,3,3-trimethylpentane and 2,3,3-trimethylbutane as compared to all other methods of purification. They studied the adsorption of isomeric hydrocarbons, including geometrical isomers and binary mixtures of paraffin-paraffin, paraffin-naphthene, and naphthene-naphthene types, and recommended it as a general method of separation.…”
Section: Industrial Aspects Of Equilibrium Adsorptionmentioning
confidence: 99%